Herstellung und Charakterisierung von Wood-Plastic-Composites (WPC) mit einer Matrix aus thermoplastischen Polyurethanen zur Erzeugung einer Holz-WPC-Verbundstruktur - Richters, Maximilian

Filling and Flow Behavior of Novel Wood-Filled Thermoplastic Elastomers - Moritzer, Elmar; Richters, Maximilian

Analysis of the Segregation Phenomena of Wood Fiber Reinforced Plastics - Moritzer, Elmar; Flachmann, Felix; Richters, Maximilian; Neugebauer, Marcel (Journal of Composites Science)

Analysis of the Segregation Phenomena of Wood Fiber Reinforced Plastics - Moritzer, Elmar; Flachmann, Felix; Richters, Maximilian; Neugebauer, Marcel (Journal of Composites Science)
Wood–plastic composites (WPC) are enjoying a steady increase in popularity. In addition to the extrusion of decking boards, the material is also used increasingly in injection molding. Depending on the formulation, geometry and process parameters, WPC tends to exhibit irregular filling behavior, similar to the processing of thermosets. In this work, the influence of matrix material and wood fiber content on the flow, mold filling and segregation behavior of WPC is analyzed. For this purpose, investigations were carried out on a flow spiral and a sheet cavity. WPC based on thermoplastic polyurethane (TPU) achieves significantly higher flow path lengths at a wood mass content of 30% than polypropylene (PP)-based WPC. The opposite behavior occurs at higher wood contents due to the different shear thinning behavior. Slightly decreased wood contents could be observed at the beginning of the flow path and greatly increased wood contents at the end of the flow path, compared to the starting material. When using the plate cavity, flow anomalies in the form of free jets occur as a function of the wood content, with TPU exhibiting the more critical behavior. The flow front is frayed, but in contrast to the flow spiral, no significant wood accumulation could be detected due to the shorter flow path lengths.
Keywords: Engineering (miscellaneous); Ceramics and Composites

Characterization of wood-filled thermoplastic polyurethane for the injection modling process - Moritzer, Elmar; Richters, Maximilian (Journal of Applied Polymer Science)

Mit dem Schraubblind-Durchsetznieten Metallteile mit Composites bei einseitiger Zugänglichkeit verbinden - Moritzer, Elmar; Richters, Maximilian; Hillemeyer, Johannes; Krassmann, Dimitri (Joining Plastics)

Characterization of wood-filled thermoplastic polyurethanes for the injection molding process - Moritzer, Elmar; Richters, Maximilian (Journal of Applied Polymer Science)

Injection Molding of Wood-Filled Thermoplastic Polyurethane - Moritzer, Elmar; Richters, Maximilian (Journal of Composites Science)